Faculty Members' Perceptions of Rigor in Dual Enrollment, Accelerated Programs, and Standard Community College Courses. Issue 169 (March 2015) - Ferguson, Colin; Baker, Pete; Burnett, Dana; Taylor, Jason L.; Pretlow, Joshua
<x xml:space="preserve">Abstract</x> This chapter presents the results of a study that investigated faculty members' views on the level of academic rigor in three settings at one community college: dual enrollment, accelerated programs, and standard community college courses.